Deaf Parents Supporting Hearing Children Language and Literacy Development: A Narrative Retrospective Study - Musyoka, Millicent M; Anderson, Sarah (Advances in Social Sciences Research Journal, 2024)
For most children, home is their first school, and their mother is the first teacher. The current research study, focusing on hearing Children of Deaf Adults (CODA), explored how Deaf parents support their hearing children's language and literacy development and how hearing children of Deaf parents experience language and literacy development within a sign language home environment. The research employed qualitative narrative research to collect data from Deaf parents and hearing children of Deaf parents. The study involved four whites (three female and one male) and two female African Americans ages 22-45. All the participants were from the Southern United States. The data was analyzed using a thematic analysis.